Celiac disease and its oral manifestations: a literature review (Research, Society and Development, 2022)
Aim: The present study aims to highlight the current understanding and literature evidence about the oral presentations of celiac disease. Methodology: The search was conducted in PubMed/MedLine and gray literature (Scholar Google) databases in September 2021. Medical Subject Headings (MeSH - Pubmed) was used to define the descriptors, in English and Portuguese, and the search strategy retrieved only studies with human beings. The descriptors applied were: "celiac disease", "dental abnormalities", "enamel defects", and "oral manifestations". Articles published in the last ten years were screened. Results: A total of 23 articles were found, of which 14 were chosen for the review. The study had a sample composed of 2323 patients. Conclusion: Recognition of the oral manifestations of celiac disease plays a key role in the early diagnosis of this condition. This study highlighted a significant association between enamel development defects, aphthous stomatitis and xerostomia as signs suggestive of celiac disease manifestation.